Doubling Down on Accountability in Europe: Prosecuting ‘Terrorists’ for Core International Crimes and Terrorist Offences Committed in the Context of the Conflict in Syria and Iraq - Mehra, Tanya (Perspectives on terrorism, 2023)
This article examines the prosecution of members of ISIL/Da’esh and other designated terrorist groups for both core international crimes and terrorist offences in the context of the conflict in Syria and Iraq. It discusses the different core international crimes that both male and female terrorists have been convicted for, the different prosecutorial strategies that have been used, and the sentences that have been imposed in several European countries. While prosecuting membership offences and other terrorist offences has certain advantages, this article argues that pursuing charges for core international crimes in addition to terrorist offences leads to a more complete accountability.